Role of circulating inflammatory protein in the development of diabetic renal complications: proteome-wide Mendelian randomization and colocalization analyses - Liu, Wenli; Zhang, Jiaqi; Zhang, Duo; Zhang, Lei (Frontiers in Endocrinology, 2024)
Background Diabetes ranks among the most widespread diseases globally, with the kidneys being particularly susceptible to its vascular complications. The identification of proteins for pathogenesis and novel drug targets remains imperative. This study aims to investigate roles of circulating inflammatory proteins in diabetic renal complications. Methods Data on the proteins were derived from a genome-wide protein quantitative trait locus (pQTL) study, while data on diabetic renal complications came from the FinnGen study. In this study, proteome-wide Mendelian randomization (MR) and colocalization analyses were used to assess the relationship between circulating inflammatory proteins and diabetic renal complications. Results MR approach indicated that elevated levels of interleukin 12B (IL-12B) (OR 1.691, 95%CI 1.179–2.427, P=4.34×10-3) and LIF interleukin 6 family cytokine (LIF) (OR 1.349, 95%CI 1.010–1.801, P=4.23×10-2) increased the risk of type 1 diabetes (T1D) with renal complications, while higher levels of fibroblast growth factor 19 (FGF19) (OR 1.202, 95%CI 1.009–1.432, P=3.93×10-2), fibroblast growth factor 23 (FGF23) (OR 1.379, 95%CI 1.035–1.837, P=2.82×10-2), C-C motif chemokine ligand 7 (CCL7) (OR 1.385, 95%CI 1.111–1.725, P=3.76×10-3), and TNF superfamily member 14 (TNFSF14) (OR 1.244, 95%CI 1.066–1.451, P=5.63×10-3) indicated potential risk factors for type 2 diabetes (T2D) with renal complications. Colocalization analysis supported these findings, revealing that most identified proteins, except for DNER, likely share causal variants with diabetic renal complications. Conclusion Our study established associations between specific circulating inflammatory proteins and the risk of diabetic renal complications, suggesting these proteins as targets for further investigation into the pathogenesis and potential therapeutic interventions for T1D and T2D with renal complications.